PELAKSANAAN PRINSIP IKTIKAD BAIK PEMEGANG KARTU KREDIT DIKAITKAN DENGAN PERJANJIAN JUAL BELI - T. SYAH MUHAMMAD PARUNGGIT (PREMISE LAW JURNAL, 2016)
A credit card is one of the facilities for facilitating buying and selling   transaction which involves a bank or a company as the publisher, credit card holders, and sellers. In practice, however, the use of credit cards is determined by the good faith of the parties concerned in taking their responsibilities since it is not possible that there is a default in the contract conducted especially by the credit card holders. The aim of the research was to explain the purchase agreement by using credit cards, the implementation of good faith principle by the credit card holders related to the purchase agreement, and the legal consequences of using credit cards when there is a default by the credit card holders. The research used descriptive analytic method and judicial normative approach which described and analyzed the implementation of good faith principle of credit card holders related to purchase agreement. Keywords :      Good Faith Principle of Credit Card Holders in Purchase Agreement